The oral contraceptive cycle and its influences on maximal and submaximal endurance parameters in elite handball players - Mathy, Astrid; Wessner, Barbara; Haider, Patricia; Tschan, Harald; Triska, Christoph (Frontiers in Physiology, 2024)
The usage of the oral contraceptive pill is widely spread across athletes of various levels. However, there is little knowledge on how the intake of the pill alters thein submaximal as well as maximal endurance parameters between the oral contraceptive phases. Therefore, aim of this study therefore was to examine potential differences between pill intake and withdrawal phase on endurance related parameters in first division handball players. In total, 15 female team handball players performed two graded exercise tests until volitional exhaustion on a motorised treadmill. Tests were performed during pill intake (day 16-17) and during withdrawal phase (day 2-3). Throughout the test, respiratory gases were measured breath-by-breath and heart rate was measured continuously. Before and after the graded exercise test blood samples were obtained in order to assess blood lactate concentration. Before each test, venous blood samples were taken to determine endogenous sex hormone levels. Ventilatory parameters (V ̇O2, V ̇CO2, V ̇E, respiratory equivalents for V ̇O2 and V ̇CO2) were measured as well as oxidation of fat and carbohydrates was calculated. A paired-samples t-test was used to assess differences between the two timepoints and significance was accepted as P<0.050. Significant differences with higherlower values during withdrawalconsumption phase were found for absolute (mean difference ± SD: 88±131 mL•min -1 ; P=0.021) and relative V ̇O2peak (mean difference ± SD: 1±2 mL•min -1 •kg -1 ; P=0.012). Higher values during consumption phase were found as well as for submaximal respiratory equivalents for V ̇O2 (mean difference ± SD: -1.1±1.7; P=0.028) and V ̇CO2 (mean difference ± SD: -0.9±1.5; P=0.032). No differences were found for all other parameters, including differences for endogenous sex hormones (P>0.050). The results of the current study suggest only marginal and physiologically meaningless insignificant differences in endurance related parameters between oral contraceptive phases.